Does history of Polish psychology exist? Multiple facets of the history of psychology - ZEIDLER, WŁODZISŁAW (Studia Psychologica: Theoria et praxis, 2016)
The reason for the question in the title is that during the First World War, Poland was not an independent country so there was no official Polish psychology contribution in the war effort. Nevertheless, psychology was allowed to be developed at two universities (Cracow and Lvov) as an academic discipline. On the other hand, in the areas under Russian jurisdiction the development of psychology started as a practical discipline (organization of psychologists – Polish Psychological Society, care for children with special needs – Szyc, Grzegorzewska). In the areas that would soon become Polish again, as early as at the beginning of the 20th century, psychology was being developed in Polish language and it served exclusively peaceful purposes (education, manufacturing) for the future independent state. That means, that as opposed to other “European psychologies” before and after the First World War, Polish psychology did exist and was developed strictly for peaceful purposes.